Assessing Tourist Satisfaction with Tourism Infrastructure in Sawangan and Kaliangkrik Sub-districts, Magelang Regency - Wahid Akhsin Budi Nur Sidiq; Inaya Sari Melati; Asep Ginanjar; Siti Ekowati Rusdini; Fulia Aji Gustaman; Nasir Nayan; Yoris Adi Maretta (Centre of Excellence in Tourism Udayana University, 2026)
Infrastructure is a key driver of regional development that supports economic growth, social welfare, and the competitiveness of local tourist destinations. However, it is often not fully realized in various tourist destinations, such as in Magelang Regency. This study aims to measure the Tourism Infrastructure Service Satisfaction Index (IKLI) in Sawangan and Kaliangkrik Subdistricts, Magelang Regency. The research method employs a combination of quantitative and qualitative approaches, with the population consisting of residents, visitors, infrastructure users, and tourism managers. The sample was determined using purposive sampling, comprising 300 respondents across 17 tourist sites. Data collection involved questionnaires, interviews, and field surveys. The IKLI dimensions consist of four categories of satisfaction levels: accessibility, tourism facilities, public facilities, and supporting infrastructure. Data analysis used a 1–4 likert scale for each IKLI parameter. The IKLI scores indicated the highest satisfaction level for supporting infrastructure (3.04/C), while tourism facilities (2.67/C) and public facilities (2.64/C) had nearly identical scores (less satisfactory). Meanwhile, the lowest level of satisfaction was found in accessibility (2.55/D), caused by narrow roads and damaged road surfaces leading to several destinations, such as Nepal Van Java, Silancur Highland, Mangli Skyview, and Negeri Khayangan. These findings highlight the need for targeted infrastructure improvements, particularly in accessibility, public facilities, and tourism facilities, to support sustainable tourism development.